Cisco Packet Tracer as a Learning Medium to Improve Student Motivation in Basic Computer Networking - Muhammad Nurfauzi; Safiuddin Parenrengi; Sukmawati (PT. Global Research Collaboration, 2026)
This study aims to analyze the effect of using Cisco Packet Tracer learning media on the learning motivation of 10th grade students at SMK Negeri 2 Gowa. The study uses a quantitative approach with a quasi-experimental design. Data collection was conducted through the distribution of questionnaires to measure students' learning motivation levels before and after the use of learning media, as well as observations to support the quantitative results obtained. The results of the study indicate that there was an increase in student learning motivation after the implementation of Cisco Packet Tracer learning media. This media allows students to perform interactive computer network simulations, making learning more interesting and easier to understand. The use of Cisco Packet Tracer provides a more contextual learning experience, particularly in computer and network engineering skills. Thus, this technology-based simulation media can be used as an effective learning alternative to increase student learning motivation in vocational high schools.